2019
DOI: 10.1021/acsphotonics.9b00251
|View full text |Cite
|
Sign up to set email alerts
|

Complete Control of Smith-Purcell Radiation by Graphene Metasurfaces

Abstract: Smith-Purcell radiation results from charged particles that move closely to a periodic structure. In this work, we report the on-demand control of Smith-Purcell radiation by rationally designed graphene metasurfaces. Not only can we strongly enhance the efficiency of Smith-Purcell radiation, but also the amplitude, phase, and polarization state of the radiated wave can be fully manipulated by tuning the structure and Fermi level of the graphene metasurface. Through designing the geometric parameters of each un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 57 publications
0
36
0
Order By: Relevance
“…The Fermi energy was varied from 0.1 eV to 1.1 eV and the corresponding frequency responses are plotted in Fig.3. It can be observed that the increase of the Fermi energy shifts the resonant frequency to higher values [21]- [23]. With change of F between 0.1 eV and 1.1 eV, the resonant frequency ranges from 5 THz to 15.96 THz for the dipole mode, from 7.2 THz to 22.56 THz for the quadrupole mode and from 8.2 THz to 25.9 THz for the hexapole one.…”
Section: Resonant Frequency Versus Fermi Energymentioning
confidence: 95%
“…The Fermi energy was varied from 0.1 eV to 1.1 eV and the corresponding frequency responses are plotted in Fig.3. It can be observed that the increase of the Fermi energy shifts the resonant frequency to higher values [21]- [23]. With change of F between 0.1 eV and 1.1 eV, the resonant frequency ranges from 5 THz to 15.96 THz for the dipole mode, from 7.2 THz to 22.56 THz for the quadrupole mode and from 8.2 THz to 25.9 THz for the hexapole one.…”
Section: Resonant Frequency Versus Fermi Energymentioning
confidence: 95%
“…[162][163][164][165] For example, vanadium dioxide (VO 2 ), a thermal-sensitive phase change material, has been demonstrated successfully for beam scanning 166 or polarization switching. 167 On the other hand, applying electric elds is arguably the most direct and preferred method to realize dynamic control in liquid crystals, 168 graphene, 89,155,[169][170][171][172] and ITO. 173 Electrical reprogrammable holograms have been demonstrated in microwave frequencies by integrating electric diodes into the unit cells of metasurfaces.…”
Section: Dynamic Control Of the Metasurfacesmentioning
confidence: 99%
“…that utilizes interband interaction), and the resonance is shifted to shorter wavelength when increasing the amplitude of Fermi energy. It should be noted that metasurfaces using patterned graphene structures have been proposed and demonstrated, aiming to manipulate and steer free‐space light in the THz and infrared regime …”
Section: Polaritons In 2d Materialsmentioning
confidence: 99%
“…It should be noted that metasurfaces using patterned graphene structures have been proposed and demonstrated, aiming to manipulate and steer free-space light in the THz and infrared regime. [140][141][142][143] Although high modulation depth (≈90%) has been achieved, [98,133,136] the graphene modulators mentioned above cannot achieve low insertion loss and high modulation depth simultaneously. Another problem is that a large bias voltage, up to several tens or even one hundred volts, is needed to efficiently tune the Fermi energy of graphene.…”
Section: Applications Of Graphene Sppsmentioning
confidence: 99%